2015
DOI: 10.2337/db15-0210
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic UCP1 Overexpression in White Adipose Tissue Improves Insulin Sensitivity in Lou/C Rats, a Model of Obesity Resistance

Abstract: Brown adipose tissue (BAT), characterized by the presence of uncoupling protein 1 (UCP1), has been described as metabolically active in humans. Lou/C rats, originating from the Wistar strain, are resistant to obesity. We previously demonstrated that Lou/C animals express UCP1 in beige adipocytes in inguinal white adipose tissue (iWAT), suggesting a role of this protein in processes such as the control of body weight and the observed improved insulin sensitivity. A β3 adrenergic agonist was administered for 2 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 45 publications
7
30
2
Order By: Relevance
“…Higher levels of UCP1 and Complex I in the BAT detected here indicate a sustained effect of CL-316,243 on BAT thermogenesis after a onemonth chronic treatment in old mice. This is consistent with strong previous evidence that β3AR stimulation leads to increased thermogenic activity of BAT in young mice (Labbé et al, 2016;Poher et al, 2015;Xiao et al, 2015) and humans as well (Cypess et al, 2015;Loh et al, 2018). It also shows that chronic β3AR administration does not induce significant receptor desensitization, despite decreased levels of BAT β3AR following treatment, in agreement with previous works (Nedergaard and Cannon, 2013).…”
Section: β3ar Agonist: a Two In One Strategy To Target Both Metabolicsupporting
confidence: 93%
See 1 more Smart Citation
“…Higher levels of UCP1 and Complex I in the BAT detected here indicate a sustained effect of CL-316,243 on BAT thermogenesis after a onemonth chronic treatment in old mice. This is consistent with strong previous evidence that β3AR stimulation leads to increased thermogenic activity of BAT in young mice (Labbé et al, 2016;Poher et al, 2015;Xiao et al, 2015) and humans as well (Cypess et al, 2015;Loh et al, 2018). It also shows that chronic β3AR administration does not induce significant receptor desensitization, despite decreased levels of BAT β3AR following treatment, in agreement with previous works (Nedergaard and Cannon, 2013).…”
Section: β3ar Agonist: a Two In One Strategy To Target Both Metabolicsupporting
confidence: 93%
“…Since CL-316,243 is well known to improve thermogenesis capacity in mice (Labbé et al, 2016;Poher et al, 2015;Xiao et al, 2015), we then verified whether it was also effective in old NonTg and 3xTg-AD mice. First, interscapular BAT weight was slightly lower in 3xTg-AD compared to NonTg mice, but was not affected by the treatment (Fig.…”
Section: β3ar Stimulation Increases Brown Adipose Tissue Thermogenesismentioning
confidence: 88%
“…[41] Previous studies have shown that UCP1 ablation can induce the occurrence of obesity and that upregulation of UCP1 can make it easier for the body to consume lipids under the same conditions to achieve the weight loss. [24,42,43] Therefore, losing weight through lipid browning is a way to change the balance point of lipid metabolism, which can enable the body to achieve a new lipid metabolism balance in the direction of slimming rather than just improving lipid consumption. [44] Since obesity is so similar to ccRCC, this phenomenon might also exist in ccRCC.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…[22,23] Lipid browning could destroy energy homeostasis to consume lipids without producing ATP energy, and UCP1 is the most important marker of lipid browning. [24] Immunofluorescence analysis and western blot showed that UCP1 was upregulated in cells stably overexpressing PLCL1 ( Figure 2E; Figure 3E,F, Supporting Information), suggesting that lipid browning might take place in these cells. PLCL1 may promote tumor cell "slimming" by activating a reaction similar to lipid browning.…”
Section: Plcl1 Repressed Ccrcc Progression and Promoted Tumormentioning
confidence: 98%
“…It is chiefly expressed in brown adipose tissue, where it regulates thermogenesis and energy expenditure while also protecting against oxidative stress20. Lactate is also known to control UCP1 expression by inducing browning in human and murine white adipocytes, and UCP1 overexpression improves insulin sensitivity in obesity-resistant rats4647. Previous work with rat muscle demonstrated that lactate can drive mitochondrial gene expression and promote fatty acid oxidation, mitochondrial activity, and expression of UCP145.…”
Section: Discussionmentioning
confidence: 99%